2010
DOI: 10.1002/pssr.200903396
|View full text |Cite
|
Sign up to set email alerts
|

Efficient spectrally dynamic blue‐to‐green emission of bipyridine‐based bridged silsesquioxanes for solid‐state lighting

Abstract: We report a metal‐free bpy‐bridged silsesquioxane displaying an efficient and tuneable blue‐to‐green emission (maximum quantum yield and luminance values of 0.22 ± 0.02 cd m–2 and 63 ± 3 cd m–2, respectively) when excited by commercial InGaN light emitting diodes (LEDs) (385–405 nm). This is the highest quantum yield value reported so far for metal‐free phosphors easily excited by commercial InGaN long‐UV/blue LEDs bringing organic/inorganic hybrids on the way to applications as metal‐free phosphors for smart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…30,31 From the point of view of materials science, the main challenge in solid-state lighting is the development of novel phosphors that collect the blue light from long UV/blue LEDs and efficiently convert it into the other colours needed for white light emission. The phosphors should, therefore, display the following requests:…”
Section: Hybrids For Lightingmentioning
confidence: 99%
“…30,31 From the point of view of materials science, the main challenge in solid-state lighting is the development of novel phosphors that collect the blue light from long UV/blue LEDs and efficiently convert it into the other colours needed for white light emission. The phosphors should, therefore, display the following requests:…”
Section: Hybrids For Lightingmentioning
confidence: 99%
“…A low-relative intensity band between 360 and 450 nm (more evident in the excitation spectrum of M-Eu) is also discerned. While the low-wavelength region (240 to 360 nm) is related to the excited states of the bpy-ligands, [14,21,25] the high-wavelength one (360 to 450 nm) is associated with the excited states of the NH=C¼O groups and of the siliceous nanoclusters, [22][23][24] as shown in the excitation spectra monitored within the hybrid emission (Fig. 7).…”
mentioning
confidence: 97%
“…6) and in a urea-bpy bridged silsesquioxane derived from the same precursor under different nucleophilic conditions. [21] Time-resolved experiments demonstrated that this emission is ascribed to a superposition of three distinct components: i) bpy triplet state (at ca. 450 nm, room temperature lifetime of 10 À5 -10 À4 s); electron-hole recombinations originated in the ii) NH=C¼O groups of the urea cross-linkages (ca.…”
mentioning
confidence: 99%
“…The spectra were collected over the 3200À300 cm À1 range by averaging 200 scans at a maximum resolution of 4 cm À1 . Curve-fitting procedures: To evaluate broad FT-IR and FTRaman bands and to identify underlying spectral components, the iterative least-squares curve-fitting procedure in PeakFit (version 4) 25 was used. The best fit of the experimental data was obtained by varying the frequency, bandwidth, and intensity of the bands and by using Gaussian/Voight shapes.…”
Section: Scheme 1 Synthetic Scheme Of the Reactionmentioning
confidence: 99%
“…15,16 When the synthetic procedure used to prepare L12 was adopted and Eu 3+ ions were incorporated (introduced as europium chloride (EuCl 3 )) (molar ratio P12/H 2 O/HCl/EuCl 3 = 1:600:0.2:x, where x = 0.05, 0.95, and 2.9), a photoluminescent lamellar BS (Eu@L12) was formed. 15 The combination of NH 4 16 The influence of the type of solvent was emphasized more recently. 17 When the synthetic route employed to prepare L12 was combined with the incorporation of a large excess of dimethylsulfoxide (DMSO) (molar ratio P12/H 2 O/DMSO/ HCl = 1:527:388:0.175), a material with a microsphere-like shape that mimics sea sponges was produced (L12D).…”
Section: Introductionmentioning
confidence: 99%